An investigation of bottom ash as a pozzolanic material. (20th October 2018) - Abdulmatin, Akkadath; Tangchirapat, Weerachart; Jaturapitakkul, Chai
Graphical abstract: Highlights: Unmodified bottom ash (BA) is not a good pozzolan. Ground BA can be used as a pozzolan in the same way as fly ash. Ground BA mortar had strength activity index higher than 100% after 28 days. This result can be used as a guideline to use ground BA as a pozzolan in concrete. Abstract: Fly ash has been widely used as a pozzolan, but a huge quantity of bottom ash (BA) has been disposed in landfills every year. Therefore, this paper addresses the development and recommendation of using BA as a pozzolanic material. Mortar containing BA at a replacement rate of 20% by weight was used to study the pozzolanic properties. The results showed that the BA needed to have particles retained on a No. 325 (45-µm) sieve at least 25% by weight to achieve the requirements for pozzolan class C and F as specified by ASTM C618 . The mortar containing BA from which the particles retained on a No. 325 sieve of 5% by weight produced better compressive strength than control mortar after 28 days. Additionally, BA from several sources had chemical properties favorable for acting as a pozzolanic material. This study's findings demonstrated that that BA with a proper fineness could be used as a pozzolanic material according to ASTM C618 . The utilization of BA is a good solution for the added value, as well as the reduction of BA in landfills.